Entornos virtuales de aprendizaje lúdico para el fortalecimiento de la dimensión socioafectiva (2018)
In order to face the technological and pedagogical changes, the teaching staff needs new competences and work models not previously required. This review addresses the incorporation of ICT in education, from the public policies that promote them, presenting its impact on the teaching, learning and development of socio-affectivity in first-grade students, its role in relation to the information society, the challenges of inclusive education, as well as emerging technologies. This project seeks to design a virtual learning environment for the strengthening of the socio-affective dimension of elementary school students, and to diagnose the socio-affective relationships of primary school students of the Antonia Santos Educational Institution. In these training spaces supported by ICT, a new way of establishing a communicative encounter between the actors of the process is proposed, where technology constitutes a decisive element to carry out actions that lead to training and learning, such as: representation of contents, realization of activities, teacher-student and student-student interactions, the evaluation of learning, among others. In order to face the technological and pedagogical changes, the teaching staff needs new competences and work models not previously required. This review addresses the incorporation of ICT in education, from the public policies that promote them, presenting its impact on the teaching, learning and development of socio-affectivity in first-grade students, its role in relation to the information society, the challenges of inclusive education, as well as emerging technologies. This project seeks to design a virtual learning environment for the strengthening of the socio-affective dimension of elementary school students, and to diagnose the socio-affective relationships of primary school students of the Antonia Santos Educational Institution. In these training spaces supported by ICT, a new way of establishing a communicative encounter between the actors of the process is proposed, where technology constitutes a decisive element to carry out actions that lead to training and learning, such as: representation of contents, realization of activities, teacher-student and student-student interactions, the evaluation of learning, among others